Annealing effect on dielectric and leakage current characteristics of Mn-doped Ba0.6Sr0.4TiO3 thin films as gate insulators for low voltage ZnO thin film transistor - Kang, KyongTae; Kim, Il-Doo; Lim, Mi-Hwa; Kim, Ho-Gi; Hong, Jae-Min (ELSEVIER SCIENCE SA, 2008)
We report on the dielectric properties and leakage current characteristics of 3 mol% Mn-doped Ba0.6Sr0.4TiO3 (BST) thin films post-annealed up to 600 degrees C following room temperature deposition. The suitability of 3 mol% Mn-doped EST films as gate insulators for low voltage ZnO thin film transistors (TFTs) is investigated. The dielectric constant of 3 mol% Mn-doped BST films increased from 24 at in-situ deposition up to 260 at an annealing temperature of 600 degrees C due to increased crystallinity and the formation of perovskite phase. The measured leakage current density of 2 3 mol% Mn-doped BST films remained on the order of 5 x 10(-9) to 10(-8) A/cm(2) without further reduction as the annealing temperature increased, thereby demonstrating significant improvement in the leakage current characteristics of in-situ grown Mn-doped BST films as compared to that (5 x 10(-4) A/cm(2) at 5 V) of pure BST films. All room temperature processed ZnO-TFTs using a 3 mol% Mn-doped BST gate insulator exhibited a field effect mobility of 1.0 cm(2)/Vs and low voltage device performance of less than 7 V (C) 2007 Elsevier B.V. All rights reserved.
Keywords: ELECTRICAL-PROPERTIES; ORGANIC TRANSISTORS; IMPROVEMENT